Pengenalan Trichoderma sp. sebagai Solusi Pengendalian Penyakit Layu Fusarium pada Tanaman Cabai di Kecamatan Grabagan, Tuban - Firlandiana, Maulidi; Mustikaningrum, Dhina; Suprayitno, Suprayitno; Kristiawan, Kristiawan; Maimunah, Maimunah; Setyana, Abdi Dewi; Prasetya, Hery; Subiyanto, Subiyanto (Abdibaraya, 2024)
Trichoderma sp. is a type of fungus that exists in the root zone of plants and is able to protect plants from disease. This biological agent is known to be able to overcome the attack of fusarium wilt which often attacks chili plants. Tuban Regency became a chili center area because in 2022 it managed to produce 36,528 tons of cayenne pepper and 6,760.98 tons of large chili. One of the sub-districts in Tuban Regency that has the highest chili production rate is Grabagan Sub-district with a production rate of 81.91%. The high rate of chili production, both cayenne pepper and large chili, is proportional to the increasing challenges of chili cultivation. This community service activity has the main objective of introducing biopesticides from the biological agent Trichoderma sp. to chili farmers in Grabagan District, Tuban Regency as a solution to chili wilt disease caused by the fungus Fusarium sp. Community Service activities initiated by the Faculty of Agriculture Lecturer Team of Sunan Bonang University Tuban have been carried out by involving 13 chili farmers in Grabagan District at the Grabagan District Extension and Food Security Center (BPKP). This activity contains counseling related to the propagation of Trichoderma sp. fungi in a simple way and sustainable agriculture with the concept of Back to Nature. The activity was complemented by hands-on practice of Trichoderma sp. fungi propagation using rice as a substrate. Based on the questionnaire distributed to the participants, it was found that 10 out of 13 chili farmers in Grabagan sub-district still depend on the use of synthetic pesticides. After receiving the counseling, 12 out of 13 chili farmers expressed their willingness to implement environmentally friendly agriculture by utilizing biological agents Trichoderma sp.